3D FEM model development from 3D optical measurement technique applied to corroded steel bars. (15th October 2016) - Fernandez, Ignasi; Bairán, Jesús Miguel; Marí, Antonio R.
Highlights: 3D optical measurement for corrosion characterization and 3D finite element method (FEM) model development. Study of the local effects of pits on the corroded mechanical properties under cyclic and monothonic loads. Fibre model validation for fast simulation of mechanical properties of corroded steel bars. Abstract: Understanding the mechanical effects of the corrosion pits on the steel surface requires an accurate definition of their geometry and distribution along the rebar. 3D optical measurement technique is used to obtain the outer geometry of artificially corroded bars tested under cyclic or monotonic loads. 3D FEM model development from the 3D scanning results were carried out in order to investigate the failure process and local effects on the pits, which are responsible of the variation of the mechanical properties in corroded steel reinforcement. In addition, a validation of a simplified model, which allows the mechanical steel properties determination given an estimated corrosion level, is presented. 3D models were convenient to observe and measure the local effects on the pits.